1999
DOI: 10.1007/s003600050234
|View full text |Cite
|
Sign up to set email alerts
|

Fat transfer and energetics during lactation in the hooded seal: the roles of tissue lipoprotein lipase in milk fat secretion and pup blubber deposition

Abstract: Hooded seals (Cystophora cristata) lactate for 3.6 days during which females simultaneously fast and transfer large amounts of energy to their pups through fat-rich milk. Pups grow rapidly, principally due to blubber deposition. Lipoprotein lipase (LPL), the primary enzyme responsible for tissue uptake of triglyceride fatty acids, may strongly influence both maternal milk fat secretion and pup blubber deposition. We measured the energetic costs of lactation (using hydrogen isotope dilution, 3H2O), milk composi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(55 citation statements)
references
References 54 publications
6
49
0
Order By: Relevance
“…Interestingly, elephant seals maintain rates of glucose production and use more glucose than expected for an animal enduring such a prolonged fast (Champagne et al, 2005). The present study suggests that northern elephant seal pups possess robust mechanisms to regulate circulating lipids, a characteristic that may not be shared by other seals; for example, fasting duration decreases NEFA concentration in grey and hooded seal pups (Iverson et al, 1995;Mellish et al, 1999). These mechanisms may include decreasing the expression of CD36 and FATP1 and increasing the expression of ATGL in adipose tissue.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Interestingly, elephant seals maintain rates of glucose production and use more glucose than expected for an animal enduring such a prolonged fast (Champagne et al, 2005). The present study suggests that northern elephant seal pups possess robust mechanisms to regulate circulating lipids, a characteristic that may not be shared by other seals; for example, fasting duration decreases NEFA concentration in grey and hooded seal pups (Iverson et al, 1995;Mellish et al, 1999). These mechanisms may include decreasing the expression of CD36 and FATP1 and increasing the expression of ATGL in adipose tissue.…”
Section: Discussionmentioning
confidence: 61%
“…This suggests a decrease in lipolysis like that observed in grey and hooded seal pups after a few days of fasting. However, the decrease in lipolysis in grey and hooded seal pups was accompanied by an expected decrease in plasma NEFA (Iverson et al, 1995;Mellish et al, 1999), not an increase as seen in elephant seal pups. It is possible that other seals may not experience similar reductions in NEFA uptake with fasting duration as that seen in elephant seal pups.…”
Section: Discussionmentioning
confidence: 67%
“…Weddell seal females certainly lose a large amount of body mass: for example, females that we studied in 2006 and 2007 lost 40% of their two-day postpartum mass during about 40 days lactation (Figure 1). The daily mass loss of 1.0% of initial mass is lower than values of 1.5%-3.4% for fasting and lactating females of the northern elephant seal, southern elephant seal, land-breeding gray seal, and hooded seal (Costa et al, 1986;Carlini et al, 1997;Mellish et al, 1999aMellish et al, , 1999b, but Weddell seal lactation is so prolonged that overall mass loss (42%) is equal to or greater than that in the other species (14%-39%). If mass loss is standardized to a lactation length of 42 days, initial mass predicts 66% of the variation in mass loss, indicating that large females lose more mass than small females (Figure 2).…”
Section: Mass Changes During Weddell Seal Lactationmentioning
confidence: 77%
“…In these species, maternal body mass and age are strong determinants of total milk energy output and, consequently, of pup growth and weaning mass (Iverson et al, 1993;Fedak et al, 1996;Arnbom et al, 1997;Mellish et al, 1999b). By contrast, females feed during a variable proportion of lactation in almost half of extant phocid species (Bonner, 1984;Oftedal et al, 1987a;Boness et al, 1994;Boness and Bowen, 1996;Lydersen and Kovacs, 1999;Eisert, 2003).…”
Section: Mass Changes During Weddell Seal Lactationmentioning
confidence: 99%
“…Although mammary gland biopsies had previously been obtained from both grey seals and hooded seals through a relatively simple modification of a 6mm tissue biopsy tool (crimping of the cutting blade on both sides) (Mellish, 1999;Mellish et al, 1999b), a pilot study we conducted in 2004 (four grey seal females) demonstrated that, because this modification did not reliably sever connective tissues within the gland, core samples of adequate size for histological examination could not be consistently obtained. Therefore, we developed a single-use biopsy instrument that could sever the tissue core (Fig.1).…”
Section: Biopsy Instrumentmentioning
confidence: 99%